(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the early outcomes of laparoscopic segmental colectomy and stapled anastomosis for rectal cancer treatment at Military Hospital 175. Subjects and Methods: This study employed a cross-sectional design, incorporating both retrospective and prospective data collection, conducted at Military Hospital 175 from January 2023 to May 2025. The study included 72 patients diagnosed with rectal cancer who underwent laparoscopic segmental colectomy using stapling devices. Results: A total of 72 patients underwent laparoscopic rectal resection with a mean age of 62.7 ± 9.7 years and a mean BMI of 24.3 ± 2.1 kg/m². Most patients were classified as stage III (58.3%), with 69.5% presenting T3 tumors. The average operative time was 166.7 ± 50.7 minutes, which correlated significantly with disease stage (p = 0.048). Gastrointestinal function recovered early, with mean times to flatus, oral intake, and defecation of 2.26, 2.25, and 2.6 days, respectively. Early postoperative complications occurred in 7.0% of patients, all of whom were managed conservatively. The mean hospital stay was 7.62 days. Conclusion: Laparoscopic rectal resection demonstrated favorable short-term outcomes, including early gastrointestinal recovery, low complication rates, and acceptable operative times, supporting its clinical applicability in rectal cancer management